2016
DOI: 10.1038/srep39460
|View full text |Cite
|
Sign up to set email alerts
|

The Angiogenic Secretome in VEGF overexpressing Breast Cancer Xenografts

Abstract: The plasticity of cancer cells and the fluidity of the tumor microenvironment continue to present major challenges in the comprehensive understanding of cancer that is essential to design effective treatments. The tumor interstitial fluid (TIF) encompasses the secretome and holds the key to several of the phenotypic characteristics of cancer. Difficulties in sampling this fluid have resulted in limited characterization of its components. Here we have sampled TIF from triple negative and estrogen receptor (ER)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…This indicates a deficiency in the disulfide-bonded form and in the total amount of these soluble factors in the secretome of ERO1 KO MDAMB231 m . Given that these are angiogenesis-related factors and are HIF-1 targets (Supplementary Table 2 ) [ 19 ], our results point to a role of ERO1 on a subset of secreted proteins which are angiogenesis-related.…”
Section: Resultsmentioning
confidence: 80%
“…This indicates a deficiency in the disulfide-bonded form and in the total amount of these soluble factors in the secretome of ERO1 KO MDAMB231 m . Given that these are angiogenesis-related factors and are HIF-1 targets (Supplementary Table 2 ) [ 19 ], our results point to a role of ERO1 on a subset of secreted proteins which are angiogenesis-related.…”
Section: Resultsmentioning
confidence: 80%
“…Here we have described findings that identify an important role of IL-8 in crosstalk between TNBC and stroma and propose IL-8 as a potential therapeutic target in TNBC. The elevated IL-8 cytokine as a tumor microenvironment factor has also been identified in the interstitial fluid collected in a tumor-implanted microchamber in TNBC xenografts, but not in ER+ xenografts, suggesting its specificity for TNBC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was reduced by CK666 treatment, with the number of mature branches that had been penetrated by tubulin also reduced. MDA MB231 release greater levels of VEGF-A versus MCF7 [ 44 , 46 ] therefore it would be expected that MDA MB231 to induce increased neurite formation as it is demonstrated that VEGF-A actions via VEGFR2 induce sensory neuron growth. However, VEGF-A alone did not induce increased collateral branching.…”
Section: Discussionmentioning
confidence: 99%